The Effect of Differentiated Learning Approach and Motivation on the Learning Outcomes (Science) of Grade V Students in Elementary School - Reni Rohayu Salman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effect of differentiated learning approaches on science learning outcomes of grade V elementary school students reviewed from the level of learning motivation. The method used is a quasi-experiment with the Nonequivalent Control Group Design. The main instruments in this study are learning outcome tests and learning motivation questionnaires. The results of the Independent Sample T-Test showed that the differentiated learning approach had a significant effect on improving science learning outcomes, with a significance value of 0.000 (< 0.05). Highly motivated students who participated in differentiated learning showed an increase in learning outcomes with an average difference of 14.64, while students with low motivation experienced a greater increase with an average difference of 21,818. Interaction analysis using the Two-Way ANOVA test showed a significant interaction between the learning approach and the level of learning motivation (Sig. = 0.020 < 0.05). These findings show that the effectiveness of differentiated learning approaches is influenced by the level of learning motivation of students. Overall, differentiated learning has been proven to be effective and inclusive in improving science learning outcomes by adapting the learning process to students' readiness, interests, and learning styles.